2011
DOI: 10.3329/jhpn.v29i4.8452
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk factors for Stunting among School Children and Adolescents in Abeokuta, Southwest Nigeria

Abstract: Stunting adversely affects the physical and mental outcome of children. The objectives of the study were to determine the prevalence of and risk factors associated with stunting among urban school children and adolescents in Abeokuta, Nigeria. Five hundred and seventy children aged 5-19 years were selected using the multi-stage random-sampling technique. Stunting was defined as height-for-age z-score (HAZ) of <-2 standard deviation (SD) of the National Center for Health Statistics reference. Severe stunting wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
101
5
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(159 citation statements)
references
References 18 publications
27
101
5
10
Order By: Relevance
“…That younger children had a better nutritional status than their older counterparts was not unexpected; similar findings have been reported in earlier studies among infant (Powell and Grantham-McGregor, 1985) and school-age populations (Senbanjo et al, 2011). We also found that the prevalence of stunting was higher in rural than periurban areas.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…That younger children had a better nutritional status than their older counterparts was not unexpected; similar findings have been reported in earlier studies among infant (Powell and Grantham-McGregor, 1985) and school-age populations (Senbanjo et al, 2011). We also found that the prevalence of stunting was higher in rural than periurban areas.…”
Section: Discussionsupporting
confidence: 77%
“…Similar patterns have been reported in earlier studies which have recorded a dramatic rise in the prevalence of stunting with age among African children (Stoltzfus et al, 1997;Hautvast et al, 2000;Senbanjo et al, 2011). Stoltzfus et al (1997) as well as Glewwe and Jacoby (1995) have postulated that, parents probably enrol the more healthy children in school at earlier ages.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations